2014
DOI: 10.1167/iovs.14-14666
|View full text |Cite
|
Sign up to set email alerts
|

Spectral-Domain Optical Coherence Tomography Study on Dynamic Changes of Human Tears After Instillation of Artificial Tears

Abstract: Spectral-domain OCT imaging has preliminarily proved to be a noninvasive tool to evaluate, in real time, the different changes induced by ATs instillation. An important stride in understanding the clinical response to various tear substitutes can be achieved by this objective and quantitative approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 26 publications
2
25
0
Order By: Relevance
“…Napoli et al. () found similar results with sodium carboxymethylcellulose and phosphosphatidylglycerol, being the residence time higher than baseline for at least 10 min.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Napoli et al. () found similar results with sodium carboxymethylcellulose and phosphosphatidylglycerol, being the residence time higher than baseline for at least 10 min.…”
Section: Discussionmentioning
confidence: 65%
“…; Napoli et al. ). Optical coherence tomography (OCT) is considered a noninvasive and practical method for imaging tear meniscus and a potential diagnostic tool for dry eye syndrome (Ibrahim et al.…”
Section: Introductionmentioning
confidence: 99%
“…The precorneal TF can also be evaluated by OCT imaging to analyze, in real time and non-invasively, the dynamic changes induced by different artificial tears (ATs). We found that the TF morphological pattern is related to the chemical composition of tear substitutes [42]. We observed a raise in OCT reflectivity when lipid concentration is augmented, and an increase in thickness with the use of water-soluble polymers.…”
Section: Structure and Appearance Of The Tear Filmmentioning
confidence: 68%
“…14,15 Miscellaneous noninvasive approaches such as confocal microscopy, interferometry, and OCT used to quantify preocular tear film thickness have shown results ranging widely from 3 to 45 mm. [16][17][18] Spectral domain OCT seems to be an objective method for assessing preocular tear film thickness, 19 the average of which in this study was approximately 22 mm. Although it is impossible to accept spectral domain OCT measurements of tear film as the gold standard, they do provide consistent, reliable data.…”
Section: Discussionmentioning
confidence: 78%